FORMATION OF PEA SEED PRODUCTIVITY DEPENDING ON SOWING RATE - Shokalo, N. S.; Bazhan, B. O.; Ozarov, A. S. (Scientific Progress & Innovations, 2020)
With appearing modern pea varieties having new morphological characteristics and high potential productivity and ability for mechanized harvesting, the necessity has arisen concerning the improvement of agro-technical measures, plant nutrition area optimization, in particular. That is why during 2018–2019, in the “Partner Agro Group” LLC of Kozelshchyna district, Poltava region, experiments were conducted on deep low humus black soil to study the sowing rates of Madonna leafless pea variety: 0.8; 1.0, and 1.2 million pcs/ha. The degree of weed infestation in the experiment’s variants was insignificant at the first calculation – 3.2–4.1 pcs/m2; it was connected with pea pre-germination harrowing, which considerably damaged one-year weeds. Before pea harvesting, the degree of weed infestation was the highest in the variant with the sowing rate of 0.8 million pcs/ha – or 34.3 pcs/m2, as the crops could not inhibit weed development because of thin sowing. At increasing sowing rate to 1.0 million pcs/ha the amount of weeds at the moment before harvesting pea made 26.1pcs/m2. The lowest weed infestation was observed in the variant with the sowing rate of 1.2 million pcs/ha or 21.7 pcs/m2. The growing period of 2018 was more favorable for pea cultivation as to weather conditions, because it was characterized by sufficient amount of moisture and warmth. During that year higher crop yields were formed, which made 2.5 t/ha on the average according to the experiment variants. During the growing period of 2019 the weather was hot, sometimes rainy. These factors affected the formation of lower pea yields – 1.8 t/ha on the average, which was 7.1 hundredweight/ha less than in 2018. The yield of 1.62 t/ha was especially lower in the variant with the sowing rate of 0.8 million pcs/ha. This was stipulated by the fact that there were the fewest number plants there, and thus, less grain was formed per area unit. On the average, during the two years of studies, the highest crop yield of Madonna pea variety was formed in the variant with the sowing rate of 1.2 million pcs/ha and made 2.4 t/ha. At decreasing the sowing rate to 1.0 and 0.8 million pcs/ha, the crop yield also decreased by 0.19 and 0.41 t/ha, or 8.1 and 17.4%.